PERANCANGAN DAN PEMBUATAN APLIKASI BANK SOAL FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS TARUMANAGARA - Lahmuddin, Adam (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
A test bank is generally known as a collection of test items or commonly referred to as question. But basically, the test bank does not only refer to the matter of collection questions only. Test bank also refers to the process of test’smonitoring and storage withrelated information to make it easier to assembled.Aplikasi Bank Soal Fakultas Teknologi Informasi Universitas Tarumanagara is an application that serves to accommodate the test that would be candidates for inclusion in the quiz/test in each course in the Faculty of Information Technology atTarumanagaraUniversity. This applicationalso provides automation features for making the testpackage. This automation using fuzzy sets to produce the prospective questions population of the test package. Kata Kunci: Bank Soal, Fakultas Teknologi Informasi Universitas Tarumanagara, Fuzzy Sets